An alternative approach to railway asset management value analysis: application to a UK railway corridor. Issue 2 (8th April 2021) - Litherland, Jack; Calvert, Gareth; Andrews, John; Modhara, Sunny; Kirwan, Andy
Abstract : Railway networks are complex systems, and the management of such systems is a challenging task for railway asset managers. It is their responsibility to ensure that the network delivers the highest level of performance for all stakeholders while adhering to strict safety regulations and financial constraints. Historically, reliability, availability, maintainability and safety (RAMS) analysis has been used to assess the performance and safety of railway networks. Nonetheless, there is a lack of consistency in approaches across the industry, with analysis often influenced by the key stakeholders at the time. This research demonstrates an application of an extended RAMS (ExRAMS) framework on the UK railway network. The ExRAMS framework aims to consolidate various extensions to the traditional RAMS approach into a single universal approach, which is beneficial to all stakeholders. This paper explores the data currently available within the rail industry and how these can be used to assess the ten metrics within the framework. The final part of the paper explores how the parameters within the ExRAMS framework can be used as the bases of a value analysis, which can then be used to assist with asset-management decisions.